Entrance and exit wounds of high velocity bullet: An autopsy analysis in the event of dispersing the mass rally in Bangkok Thailand, May 2010 - Vichan Peonim (2018)
© 2016 Elsevier Ireland Ltd Fatal mass casualties by high velocity bullets (HVBs) are rare events in peaceful countries. This study presents 27 forensic autopsy cases with 32 shots fired by 5.56 × 45 mm. HVB (M-16 rifle bullets) during the dispersing the mass rally in Bangkok Thailand, May 2010. It was found that twenty-three (71.88%) typical entrance HVB wounds had round sizes less than the bullet diameters. Most entrance wounds had microtears but no collar abrasion since a HVB has a small streamlined spitzer tip and full metal jacket. For exit wounds, there were various sizes and shapes depending on which section of wound ballistics presented when the bullet exited the body. If a bullet exited in the section of temporally cavity formation, there would be a large size exit wound in accordance with the degree of bullet yaw. This is different from civilian bullets whereby the shape looks like a cylindrical round nose and at low velocity that causes entrance wounds with a similar size to the bullet diameter and is usually round or oval shape with collar abrasion. The temporary cavity is not as large as in a HVB so exit wounds are not quite as large and present a ragged border compared to a HVB. We also reported 9 out of 32 shots (28.13%) of atypical entrance wounds that had various characteristics depending on site of injury and destabilization of bullets. These findings may be helpful to forensic pathologists and to give physicians, who need to diagnose HVB wounds, more confidence.